Optimizing anti-PD-1/PD-L1 therapy efficacy and fecal microbiota transplantation donor selection through gut mycobiome-based enterotype - Muni Hu; Xiaoqiang Zhu; Xiaowen Huang; Li Hua; Xiaolin Lin; Hangyu Zhang; Ye Hu; Tianying Tong; Lingxi Li; Baoqin Xuan; Ying Zhao; Yilu Zhou; et al. (Cell Reports)
Summary: Immunotherapy has revolutionized cancer treatment, but response variability remains a challenge. The gut microbiome’s role in therapeutic efficacy is well established, but the impact of the gut mycobiome is less understood. Using unsupervised clustering, we identify two gut mycobiome-based enterotypes, favorable type and unfavorable type, characterized by distinct microbial compositions linked to immunotherapy outcomes. Favorable-type enterotypes exhibit higher fungal and bacterial alpha diversity, enriched butyrate-producing bacteria, and metabolic pathways related to butyric acid and sugar/starch metabolism. External validation confirms their predictive value in assessing immunotherapy efficacy. Multi-omics analysis reveals increased CD8+ T cell infiltration in the tumor microenvironment of favorable-type patients. Fecal microbiota transplantation (FMT) from favorable-type donors enhances anti-PD-1 sensitivity, promotes CD8+ T cell infiltration, and boosts butyrate production in vivo. These findings highlight the gut mycobiome’s role in immunotherapy response and support FMT from favorable-type donors as a potential strategy for improving treatment outcomes and patient stratification.